Modelo de evaluación para verificar los resultados de las horas de gestión individual del docente fuera de clases en la escuela Indoamérica de Canchagua del cantón Saquisilí en el periodo 2012 - 2013 - Masapanta Changoluisa, María Elsa (2015)
The purpose of this study was to establish an assessment model for teachers at Indoamérica' Elementary School in Canchagua to provide a quality in education through exploration and analysis of the argument 'Teacher Assessment' and its impact in the improvement of quality in education. Aspects such as theoretical, social, and globalizing were taken into account. They involve the term 'evaluation' and its important aspects such as 'quality' and 'efficiency', in order to fulfill with the current design in our country. In addition, the results that teachers can achieve through the implementation of several techniques are to know their true performance regarding teaching skills, interpersonal relationships, results of their teaching, etc. Finally, this trend in the data indicates a difficult situation on the current reality within the institution and how to improve it.